Age affects the contribution of ipsilateral brain regions to movement kinematics. Issue 3 (16th October 2019) - Tscherpel, Caroline; Hensel, Lukas; Lemberg, Katharina; Freytag, Jana; Michely, Jochen; Volz, Lukas J.; Fink, Gereon R.; Grefkes, Christian
Abstract: Healthy aging is accompanied by changes in brain activation patterns in the motor system. In older subjects, unilateral hand movements typically rely on increased recruitment of ipsilateral frontoparietal areas. While the two central concepts of aging‐related brain activity changes, "Hemispheric Asymmetry Reduction in Older Adults" (HAROLD), and "Posterior to Anterior Shift in Aging" (PASA), have initially been suggested in the context of cognitive tasks and were attributed to compensation, current knowledge regarding the functional significance of increased motor system activity remains scarce. We, therefore, used online interference transcranial magnetic stimulation in young and older subjects to investigate the role of key regions of the ipsilateral frontoparietal cortex, that is, (a) primary motor cortex (M1), (b) dorsal premotor cortex (dPMC), and (c) anterior intraparietal sulcus (IPS) in the control of hand movements of different motor demands. Our data suggest a change of the functional roles of ipsilateral brain areas in healthy age with a reduced relevance of ipsilateral M1 and a shift of importance toward dPMC for repetitive high‐frequency movements. These results support the notion that mechanisms conceptualized in the models of "PASA" and "HAROLD" also apply to the motor system.